Students’ interest in physical education learning: A study of COVID-19 - Henjilito, Raffly; Putera, Nico Adhiguna; Gazali, Novri; Juita, Ardiah; Abdullah, Nagoor Meera (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
During the COVID-19 pandemic, students' interest in learning physical education was unknown. The purpose of this study is to see the extent of student interest in participating in the physical education learning process during the COVID-19 pandemic. The method used in this research is quantitative descriptive research. The population in this study consisted of 10th and 11th grade students of SMK Negeri 3 Tanjungpinang who participated in physical education lessons, and the sampling technique used in this study was total sampling, which amounted to 345 people. The test used in this study was a questionnaire test or a questionnaire test with a Likert scale. After the research was carried out, very satisfactory results were obtained, namely in a very high category. Students are very active during learning even though they are in a COVID-19 pandemic condition. Future research is expected to determine an effective approach for students who participate in physical education during a pandemic.